STUDENTS' PERCEPTION OF BULLYING BEHAVIOR AT LUQMANUL HAKIM INTEGRATED ISLAMIC MIDDLE SCHOOL, BANDUNG CITY - Qurratul'ain, Nadjeela; Suhendar, Suhendar; Tungga, Yeane Ellen Marry (Politeknik Kesejahteraan Sosial Bandung, 2025)
Perception is the process by which individuals receive and interpret stimuli through their senses as a response to specific objects or situations. This perception influences how a person understands and reacts to events, including bullying behavior. This study aims to examine: (1) students’ cognitive understanding of bullying, (2) their emotional (affective) responses to bullying, and (3) their behavioral (conative) tendencies in addressing bullying situations. The study employs a quantitative approach using a descriptive method. A total of 58 students from SMP Islam Terpadu Luqmanul Hakim in Bandung participated in the research, selected using a saturated sampling technique. Data were collected through questionnaires, documentation study, and observation to obtain a comprehensive picture. Instrument validity was ensured through face validity, while reliability was measured using Cronbach’s Alpha to assess response consistency. The findings indicate that students' perceptions of bullying are generally high. The cognitive aspect scored 83.3% (5,024), the affective aspect 81.7% (4,168), and the conative aspect 79.27% (3,678). Based on these results, the researcher developed an intervention program titled “Bullying Prevention Workshop,” which aims to enhance students’ understanding, awareness, and empathy in dealing with bullying issues within the school environment.